Driving Transparency: The Impact of Corporate Governance on Environmental Disclosure - Susanti, Lasmita; Syafaruddin, Ade Syamsul (Santoso Academy Network, 2024)
This study aims to examine the effect of Corporate Governance on Environmental Disclosure with Firm Size and Leverage as control variables. This study uses quantitative methods. This study uses secondary data that is quantitative in the form of annual financial reports listed on the Indonesia Stock Exchange (IDX). The object of this study is to identify energy sector companies listed on the IDX between 2020-2022. The data analysis method uses statistical analysis using the Multiple Linear Regression equation. Logistic regression testing. Sample selection is done by purposive sampling. The results of this study show that institutional ownership does not affect environmental disclosure, Independent commissioners have no effect on environmental disclosure, Audit committees do not affect environmental disclosure, Firm size has no effect on environmental disclosure, and Leverage has no effect on environmental disclosure. The managerial implications of the influence of corporate governance on environmental disclosure can be seen as a need for companies to improve the quality of governance to support environmental transparency and accountability. A competent, independent, and diverse board of directors plays an important role in ensuring that environmental policies are not only met as a formality but also become an integral part of the company's strategy.